2007
DOI: 10.1116/1.2433976
|View full text |Cite
|
Sign up to set email alerts
|

Leakage current and charge trapping behavior in TiO2∕SiO2 high-κ gate dielectric stack on 4H-SiC substrate

Abstract: The TiO2∕SiO2 gate dielectric stack on 4H-SiC substrate has been studied as a high-κ gate dielectric for metal-oxide semiconductor devices. X-ray photoelectron spectroscopy confirmed the formation of stoichiometric TiO2 films. The leakage current through the stack layer was investigated and it has been shown to be a double conduction mechanism. At low fields, the current is governed by properties of the interfacial layer with a hopping like conduction mechanism, while at relatively high electric field, carrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 30 publications
(24 reference statements)
3
27
0
Order By: Relevance
“…From the I − V measurements, the amorphous Al 2 O 3 thin films were found to sustain an electric field of 8.0 MV/cm with a leakage current density of ϳ10 −3 A / cm 2 . This electric field strength is higher than that of any high-dielectric material on 4H-SiC reported to date, [28][29][30][31][32][33] including AlN, HfO 2 , SiO 2 / HfO 2 , Gd 2 O 3 , oxidized Ta 2 Si, and SiO 2 / TiO 2 , and several other studies of Al 2 O 3 deposited by sputtering, 34 evaporation, 35 and ultravioletassisted ͑UV-assisted͒ ALD 36 techniques. These electrical results demonstrate the potential of thermal ALD Al 2 O 3 gate dielectrics as an alternative to the state-of-the-art thermal SiO 2 .…”
Section: Capacitance-voltage and Leakage Current Characteristicsmentioning
confidence: 51%
“…From the I − V measurements, the amorphous Al 2 O 3 thin films were found to sustain an electric field of 8.0 MV/cm with a leakage current density of ϳ10 −3 A / cm 2 . This electric field strength is higher than that of any high-dielectric material on 4H-SiC reported to date, [28][29][30][31][32][33] including AlN, HfO 2 , SiO 2 / HfO 2 , Gd 2 O 3 , oxidized Ta 2 Si, and SiO 2 / TiO 2 , and several other studies of Al 2 O 3 deposited by sputtering, 34 evaporation, 35 and ultravioletassisted ͑UV-assisted͒ ALD 36 techniques. These electrical results demonstrate the potential of thermal ALD Al 2 O 3 gate dielectrics as an alternative to the state-of-the-art thermal SiO 2 .…”
Section: Capacitance-voltage and Leakage Current Characteristicsmentioning
confidence: 51%
“…Both Al and Ta metal nucleation layers resulted in a decrease in mobility as much as 25%, while the use of a Ti seed resulted in an increase in mobility of 10-22%. 50,89,90 Shen et al 91 showed that the quantum-Hall effect (QHE) and pronounced Shubnikov-de Haas (SdH) oscillations could be observed at low temperatures in epitaxial graphene using a metal seeded ALD Al 2 O 3 gate dielectric. 1(b)].…”
Section: B Metal Seed Layersmentioning
confidence: 99%
“…Previous work has yielded moderate success with HfO2, Al2O3 and TiO2 amongst other materials. A reduced interface trap density is observed albeit with increased gate leakage due to reduced bandgap (although this may be mitigated by a SiO2 buffer layer) [1][2][3][4]. 1 shows the trade-off between bandgap and dielectric constant in typical oxide materials used on 4H-SiC alongside the significantly increased value achieved in this work.…”
Section: Introductionmentioning
confidence: 68%